Physician Satisfaction with Current Psoriasis Treatment: A Real-World Study in the USA. Issue 2 (March 2016) - Korman, Neil J.; Zhao, Yang; Roberts, Jenna; Pike, James; Sullivan, Emma
Background: Dermatologists may provide a unique perspective on psoriasis management by offering an evaluation of satisfaction with disease control. Objectives: To examine physician satisfaction with psoriasis control. Methods: Data were extracted from the Adelphi 2011/2013 Psoriasis Disease Specific Programmes, two real-world U.S. surveys of dermatologists. For individual patients, physicians reported treatment history, disease severity, symptom severity for itching, pain and scaling, and their satisfaction level (satisfied vs. dissatisfied). Results: Dermatologists were dissatisfied with disease control for 28.6% of patients. When physicians were dissatisfied, patients were more likely to currently have moderate (66% vs. 33%) or severe (20% vs. 2%) psoriasis compared to patients with satisfied physicians (p<0.05). Patients with dissatisfied physicians were also more likely to currently have more severe pain, itching and scaling, and were less likely to be receiving a biologic therapy (all p<0.05). Conclusion: Dermatologists were dissatisfied with the control achieved for more than one-quarter of their psoriasis patients.